1998
DOI: 10.1002/(sici)1097-0142(19980215)82:4<642::aid-cncr5>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of matrix metalloproteinase-2 activity in invasion and metastasis of pancreatic carcinoma

Abstract: The results of the current study indicate that MMP-2 activation plays a significant role in tumor invasion and metastasis in pancreatic carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
71
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(79 citation statements)
references
References 20 publications
7
71
0
1
Order By: Relevance
“…Similarly, expression of activated MMP-2 is related to regional lymph node and distal metastasis as well as to postresection recurrence of the same tumour. 56 Concomitant overexpression of MMP-2 and MMP-7 is associated with recurrence in hepatocellular cancer, 57 and elevated MMP-9 expression in tumor cells is related to recurrence in superficial carcinoma of the urinary bladder. 58 The expression of certain MMPs in primary tumour can predict the risk of metastasis.…”
Section: Mmps As Predictors Of Recurrence or Metastasis Riskmentioning
confidence: 99%
“…Similarly, expression of activated MMP-2 is related to regional lymph node and distal metastasis as well as to postresection recurrence of the same tumour. 56 Concomitant overexpression of MMP-2 and MMP-7 is associated with recurrence in hepatocellular cancer, 57 and elevated MMP-9 expression in tumor cells is related to recurrence in superficial carcinoma of the urinary bladder. 58 The expression of certain MMPs in primary tumour can predict the risk of metastasis.…”
Section: Mmps As Predictors Of Recurrence or Metastasis Riskmentioning
confidence: 99%
“…Thus, the net MMP activity is the result of the balance between activated enzyme levels and TIMP levels. The overproduction and unrestrained activity of MMPs have been linked to malignant conversion of tumor cells (Bernhard et al, 1994;Koshiba et al, 1998;Sehgal et al, 1998;Coussens et al, 1999;Sternlicht et al, 1999;Coussens et al, 2000). Decreased production of TIMP could also result in greater e ective enzyme activity and invasive potential (Denhardt et al, 1992;Khokha et al, 1989).…”
Section: Old Paradigm: Inhibition Of Tumorigenesis and Tumor Metastasmentioning
confidence: 99%
“…Previous studies have shown that active MMP-2 is expressed in a variety of tumour types, including gastric carcinoma [5,6], colorectal carcinoma [6], pancreatic carcinoma [7], breast cancer [8] and bladder cancer [9]. In urothelial cancer, tumour cell in®ltration into muscle layers, surrounding tissue or vessels is associated with local recurrence, metastasis and a poor outcome [10].…”
Section: Introductionmentioning
confidence: 99%